Comparison of Dye-Sensitized Solar Cells Performance using Natural Dye Sensitizer Extracted from Zingiber cassumunar and Clitoria ternatea - คำหอม สถาพร (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2018)
This research investigated the use of natural dye sensitizer extracted from Zingiber cassumunar and Clitoria ternatea for dye-sensitized solar cells (DSCs). The results showed that natural dye sensitizer on TiO2 absorbed visible light in a region with peak between 400 and 800 nm. Photoelectrochemical properties of two natural dye sensitizers were compared in the extraction conditions at constant pH of 7, with the varying of extraction mass per volume of solvent: 1, 3, 5, 7, 9, 11, 15, and 20 %w/v. It was found that the highest maximum power of DSCs of both natural dye sensitizers reached to the constant when using of 11 %w/v. Dye sensitizer from Zingiber cassumunar showed the highest maximum power of 1.493 W/cm2 at 15 %w/v while dye sensitizer from Clitoria ternatea showed the highest maximum power of 0.684 W/cm2 at 5 %w/v. The following experiment at constant of 11 %w/v, with the varying of extraction pH values: 2.4, 4.3, 7.0, 9.4, and 11.0. It was found that the highest maximum power of DSCs using both natural dye sensitizers of 1.444 and 0.700 W/cm2 at extraction pH 7.0 and 4.3, respectively. From both conditions, the photoelectrochemical properties of DSCs with dye sensitizer from Zingiber cassumunar were found to be apparently higher than that of Clitoria ternatea.